2011
DOI: 10.3389/fnhum.2011.00135
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus Fractionation by Interocular Suppression

Abstract: Can human observers distinguish physical removal of a visible stimulus from phenomenal suppression of that stimulus during binocular rivalry? As so often happens, simple questions produce complex answers, and that is the case in the study reported here. Using continuous flash suppression to produce binocular rivalry, we were able to identify stimulus conditions where most – but not all – people utterly fail to distinguish physical from phenomenal stimulus removal, although we can be certain that those two equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 42 publications
8
34
0
Order By: Relevance
“…One possibility is that, rather than suppressing all stimulus features equally, there are some which allow for making judgments of temporal information, but not for the mere presence or absence of the stimulus. In line with this suggestion, previous work has found dissociations in awareness of different stimulus features (Hong & Blake, 2009;Zadbood, Lee, & Blake, 2011). Thus, it could be that there is some rough percept which allows observers to make the order judgments with reasonable accuracy, but is not available for responding in the 2IFC task (study 2) or the complex word-nonword judgment (study 3).…”
Section: Discussionsupporting
confidence: 58%
“…One possibility is that, rather than suppressing all stimulus features equally, there are some which allow for making judgments of temporal information, but not for the mere presence or absence of the stimulus. In line with this suggestion, previous work has found dissociations in awareness of different stimulus features (Hong & Blake, 2009;Zadbood, Lee, & Blake, 2011). Thus, it could be that there is some rough percept which allows observers to make the order judgments with reasonable accuracy, but is not available for responding in the 2IFC task (study 2) or the complex word-nonword judgment (study 3).…”
Section: Discussionsupporting
confidence: 58%
“…However, this emergence into conscious awareness is not an abrupt, all-or-none phenomenon, but a gradual one (Stein et al, 2011a), and some stimulus properties become available to consciousness earlier than others. For example, recent observations have shown that, under conditions of prolonged CFS, periods of partial awareness might arise, in which some stimulus properties (such as color) are available to consciousness, whereas other are not (such as orientations; Zadbood et al, 2011; Yang and Blake, 2012). Thus, prolonged periods of continuous flash suppression might enable distinct stages of suppression strength that vary in the degree of susceptibility to experimental manipulations.…”
Section: Discussionmentioning
confidence: 99%
“…This explanation of CFS is supported by the observation that CFS suppression is more effective when the target and the mask share similar spatiotemporal properties (Yang and Blake, 2012). CFS does not “shut off” visual processing but rather selectively attenuates the activity in a subpopulation of neurons, just like other types of visual masking (Zadbood et al, 2011). We conclude that CFS affects the gain of early visual responses, consistent with the extensive literature on visual masking.…”
Section: Discussionmentioning
confidence: 99%